A Comparative Clinical Trial for Comparative Efficacy of Bhringraj Panchanga Taila Abhyanga and Nasya in Khalitya - Jadhav, Anil Govindrao; Huddar, Shreedevi (International Research Journal of Ayurveda & Yoga, 2024)
Background: Khalitya (hair fall) is a common disease in the present era associated with an unhealthy diet and lifestyle. Khalitya involves the Shiro as the Roga Adhishtana (Site of Disease). Shiro Abhyanga with Taila Kalpana is effective for all Shirorogas. Bhrungaraja has been explained as Keshya in Dhanwanthari Nighantu and Kaiyyadeva Nighantu. Hence, by taking the reference as Keshya, Bhrungaraja Taila can be made using Sneha Paka Vidhi and given to Shiro Abhyanga and Nasya Karma in cases of Khalitya. Objectives: To evaluate the comparative efficacy of Bhringraja Panchanga, Taila Abhyanga, and Nasya in different routes of administration. Materials and Methods: Shiro abhyanga was done every day with a similar method of massaging as mentioned in the classics with Bhrungaraja Taila for 15 days of duration in one group, and Marsha Nasya was administered with Bhrungaraja Taila for 7 days in the other group. Clinical signs and symptoms were given suitable scores according to their severity and assessed based on relief after treatment. The results with a P < 0.05 were considered statistically significant in this study. Results: The overall assessment of the results showed that the subjects in Group B treated with Bhrungaraja Taila Marsha Nasya responded well compared to the subjects in Group A treated with Bhrungaraja Taila Shiro Abhyanga. Interpretation and Conclusion: The clinical study revealed that the drug possesses the efficacy of Bhrungaraja Taila in Khalitya (hair fall), and thus the efficacy of Bhrungaraja Taila in this study is justified with the help of Shiro Abhyanga and Nasya Karma.